Exploratory physical education teachers’ perspectives and intentions to use VR in the classroom context: a cross-sectional qualitative study - Amoroso, José Pedro; Tsivitanidou, Olia; Sarens, Marc; Christodoulides, Efstathios; Antoniou, Kyriaki; Silva, David; Coelho, Luís; Cools, Wouter (Frontiers in Virtual Reality, 2025)
IntroductionThis study explored the potential role of emerging technologies, particularly active Virtual Reality (VR), from a Physical Education (PE) teacher’s perspective. VR technologies, which provide three-dimensional (immersive) simulation environments, have become more accessible and cost-effective in recent years. Using this technology to train students in various PE areas may add value.ObjectivesThe study aimed to understand PE teachers’ knowledge of VR and their expectations for teaching PE using VR in classroom settings. Specifically, we explored the experiences, challenges, and potential benefits perceived by PE teachers across four European countries.ParticipantsThirty-eight PE teachers from Portugal, Belgium, Italy, and Cyprus participated voluntarily.DesignThis qualitative study employed a phenomenological approach. Data were collected between March and May 2024 in public and private secondary schools with ethical approval.MethodsData was gathered through open-ended focus group questions and analysed using a thematic analysis approach.ResultsResponses revealed varied experience levels with VR. Most participants expressed a willingness to use VR in PE, showing enthusiasm for new technologies and cautious optimism about integration. While recognizing its potential, respondents highlighted limitations. Technical barriers included Internet issues, limited technical skills, and lack of IT support. These reflect the challenges of implementing VR in schools. Teachers valued VR’s potential to expose students to otherwise inaccessible sports and activities. They also discussed its use for improving specific skills, such as first aid, game tactics, and individual sports techniques.ConclusionIntegrating VR into PE presents both challenges and opportunities. Addressing training, financial, and logistical issues may enhance student engagement and learning outcomes.